Prognostic value of estrogen receptor α and estrogen receptor β in gastric cancer based on a meta-analysis and The Cancer Genome Atlas (TCGA) datasets. (May 2018) - Ge, Hua; Yan, Yan; Tian, Fei; Wu, Di; Huang, Yongsheng
Abstract: Purpose: Numbers of studies have demonstrated that estrogen receptor α and estrogen receptor β have been involved in development of gastric cancer. Hence, we analyzed studies and The Cancer Genome Atlas (TCGA) data of ERs expression and perform this meta-analysis to access the association between ERα or ER β and the clinicopathological characteristics, overall survival time, in GC. Method: A literature search was performed in PubMed, Cochrane Library, Web of Science, EMBASE database, and Chinese CNKI. Data on the relationship between ERα or ERβ expression and clinicopathological features were extracted. A TCGA dataset including information of the ERs expression and clinical data of GC patients was analyzed. Pooled odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated. Results: ERα was not associated with cancer risk, lymph node metastasis, infiltration degree, gender, and TNM stage. However, ERβ was negatively associated with lymph node metastasis. ERα expression may be associated with poor prognosis in GC patients. Conclusion: Estrogen receptors may be related to the progression and deterioration of gastric cancer. However, further high-quality studies are needed to provide more reliable evidence. Highlights: ERα and ERβ were not associated with cancer risk, infiltration degree, gender, and TNM stage. The absence of ERβ was associated with lymph node metastasis. ERα was associated with poor prognosis in GC patients. Estrogen receptors may be related to the progression and deterioration of GC.